Preliminary Analysis for Developing Digital Assessment of Science Process Skills in Occupational Health and Safety for University Chemistry Laboratory - Muhammad Bayu Kusuma; Nahadi; Budiman Anwar (Postgraduate, University of Mataram, 2025)
This study represents the initial phase in the development of a digital assessment instrument targeting science process skills (SPS) contextualized within occupational health and safety (OHS) practices in university chemistry laboratories. The objective was to identify field-based needs and formulate relevant SPS indicators through a needs analysis framework. The research adopted the Analysis phase of the ADDIE model, collecting data via field observations, student pre-assessment, semi-structured interviews with laboratory personnel, and literature and regulation reviews. Results showed that although 95.7% of students considered OHS important, only 14.9% had prior training, and most struggled with basic procedures such as proper use of personal protective equipment and chemical hazard identification. Interviews confirmed the absence of valid assessment tools integrating both SPS and safety procedures. These findings underscore the urgency of developing an interactive digital assessment aligned with educational goals and national safety regulations.